2013
DOI: 10.3748/wjg.v19.i44.8114
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopicvsopen total gastrectomy for gastric cancer: A meta-analysis

Abstract: LTG is safe and effective, and may offer some advantages over OTG in the treatment of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 40 publications
6
58
0
3
Order By: Relevance
“…One must be aware of the inevitable selection bias in such a retrospective case series. The indications for laparoscopic gastrectomy might have differed among hospitals, and more advanced cases most [29,30] and laparoscopic total gastrectomy [31]. In terms of the postoperative complication rate, four studies of five reported a 6.5-20 % risk reduction in laparoscopic approach compared to the open approach.…”
Section: Discussionmentioning
confidence: 99%
“…One must be aware of the inevitable selection bias in such a retrospective case series. The indications for laparoscopic gastrectomy might have differed among hospitals, and more advanced cases most [29,30] and laparoscopic total gastrectomy [31]. In terms of the postoperative complication rate, four studies of five reported a 6.5-20 % risk reduction in laparoscopic approach compared to the open approach.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of minimally invasive surgical methods are proven and well published [6,[10][11][12][13][14][15][16]. With advantages such as decreased postoperative pain and shorter length of hospital stay, minimally invasive techniques are heralded as a significant development in the progress of general surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] However, there are many reconstruction methods of E-J stomy for LTG. Generally, the E-J stomy methods can be divided into two main types depending on whether a circular stapling, [14][15][16][17][18][19][20][21] or linear stapling 22-29 approach was used.…”
Section: Reconstruction Methodsmentioning
confidence: 99%
“…[9][10][11][12][13] LTG and OTG were similar in terms of the number of harvested lymph nodes (LNs), resection margin, hospital mortality, and long-term outcomes. The only disadvantage of LTG was a longer operative time.…”
Section: Comparison Between Ltg and Open Total Gastrectomy (Otg)mentioning
confidence: 99%
See 1 more Smart Citation